Landslide hazard assessment in Yateras municipality, Cuba - Pospehov Georgui B.; Savón Yusmira (E3S Web of Conferences, 2024)
The main objective of this study in the Yateras municipality was the landslide hazard zonation (LHZ). The multi-criteria decision method used by Saaty (1980) was adopted, considering the factors; slope angle, elevation, distance to rivers, distance to the fault, average annual rainfall, lithology, soil depth and soil type. The weights of the factors were determined using the Analytical Hierarchy Process (AHP), determining that average annual rainfall, lithology and soil depth obtained the highest weights in the process, being 0.24, 0.19 and 0.16 respectively. Landslide susceptibility indices were determined based on a continuous numerical scale developed for this purpose. It was found that the high and medium hazard zones corresponded to the northeast and east of the municipality. These zones are mainly made up of rocks of the ophiolitic complex, very affected structurally, which are characterized by a high density of faults and a dense hydrological network, shallow soils with a predominance of brown soils with a clayey matrix.